The Iranian EFL teachers' perceptions on translation strategy use - Asgarian, Amir (Elsevier Science Bv, 2013)
The use of translation in learning a foreign language can be ignored by language teachers; but translation is widely used throughout learners' learning process. The present study; therefore, attempted to explore Iranian EFL teachers' perceptions on translation strategy use. The content analysis of the participants' qualitative reports indicated that the Iranian EFL teachers held different perceptions on the role of translation in their learning and teaching experiences, as well as their academic studies and translation/interpretation practice. Moreover, the interviewees provided interesting insights in relation to effective translation/interpretation. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ALSC 2012
Akdeniz Language Studies Conference -- MAY 09-12, 2012 -- Antalya, TURKEY
Keywords: Translation strategy; teachers' beliefs; EFL learners and teachers